Open Broström-Gould Repair vs Arthroscopic Anatomical Repair of the Anterior Talofibular Ligament for Chronic Lateral Ankle Instability. (January 2020) - Zeng, Gang; Hu, Xumin; Liu, Wenzhou; Qiu, Xuemei; Yang, Tao; Li, Chunhai; Song, Weidong
Background: The comparative studies on open vs arthroscopic anterior talofibular ligament (ATFL) repair are limited. This study aimed to compare the early therapeutic efficacy and cost between the traditional open Broström-Gould repair and all-arthroscopic anatomical repair of the ATFL for chronic lateral ankle instability. Methods: A total of 27 of patients with chronic lateral ankle instability undergoing repair of the ATFL between January 2013 and June 2015 were retrospectively included with a traditional open surgery (n = 10) group and arthroscopy (n = 17) group. The surgery duration, surgical cost, postoperative complications, and the preoperative/postoperative American Orthopaedic Foot & Ankle Society Score (AOFAS) and Karlsson-Peterson score were compared between groups. Results: Compared to the arthroscopy group, the open surgery group had significantly shorter surgery duration and lower surgical cost. However, there was no significant difference in hospitalization duration between groups. At 3 years after operation, the AOFAS and Karlsson scores were significantly improved in both groups. Nevertheless, there was no significant difference in the AOFAS and Karlsson scores between groups at both preoperative and postoperative assessment. No significant difference was found in the incidence of postoperative complications between the 2 groups. Conclusion: These results suggest that open Broström-Gould repair and all-arthroscopic anatomical repair of the ATFL have comparable therapeutic efficacy for chronic lateral ankle instability. The arthroscopic surgery had a smaller incision, while the open Broström-Gould had a shorter surgery duration and lower cost. Level of Evidence: Level III, comparative study.